Warships - Jackson, Robert 1941- (Inside out, 2019)
Arranged chronologically, this abundantly illustrated volume explores every significant warship built from the nineteenth century right up to the latest hi-tech carrier, including submarines and battleships from all the major naval powers. Each vessel includes full specs, a cutaway artwork labeled with key items of interest, accompanying photographs showing the ship's interior and exterior, and a design and development history with descriptions of active service